Systematic Literature Review on The Phenomenon of Panic Attacks in The Context of Contemporary PAI - Ummah, Khaira; Kustati , Martin; Bashori, Bashori (TOFEDU: The Future of Education Journal, 2025)
The phenomenon of panic attacks has become a significant mental health issue in contemporary society, especially among university students, and requires an integrated holistic response. This study aims to identify, analyze, and comprehensively synthesize the role, intervention models, and the relevance of contemporary PAI in responding to and preventing panic attacks and anxiety disorders. The method used is a Systematic Literature Review (SLR) with a qualitative narrative synthesis approach, collecting and analyzing relevant scientific literature sources such as journal articles and books, thus providing a comprehensive overview. The findings indicate that Islamic Religious Education (PAI) not only serves as general spiritual support but also provides a specific and effective spiritual cognitive framework. Key findings emphasize the importance of internalizing the values of Tawakkal, implementing Dhikr and prayer practices as Islamic mindfulness mechanisms, and the role of PAI teachers as cognitive spiritual counselors. The research findings also formulate a Contemporary PAI Response Model that can be integrated into the PAI curriculum to reduce physiological and cognitive catastrophic symptoms of panic attacks.